Bangladesh Rural Advancement Committee year ended 31 December 1976: financial statements and report - BRAC (© BRAC, 2016)
This Financial Statement prepared by S.F. Ahmed & Co. Chartered Accountants, 95 Motijheel, Dacca-2, Bangladesh.